Protective Role of Akt2 in Salmonella enterica Serovar Typhimurium-Induced Gastroenterocolitis - Kum, Winnie W. S. (American Society for Microbiology, 2011)
The Salmonella effector protein SopB has previously been shown to induce activation of Akt and protect epithelial cells from apoptosis in vitro. To characterize the role of Akt2 in host defense against Salmonella enterica serovar Typhimurium infection, wild-type (WT) mice and mice lacking Akt2 (Akt2 knockout [KO] mice) were infected using a Salmonella acute gastroenteritis model. Infected Akt2 KO mice showed a more pronounced morbidity and mortality associated with higher bacterial loads in the intestines and elevated levels of proinflammatory cytokines, including tumor necrosis factor alpha (TNF-α), gamma interferon (IFN-γ), and MCP-1, in the colons at 1 day postinfection compared to those shown in WT mice. Histopathological assessment and immunohistochemical analysis of cecal sections at 1 day postinfection revealed more severe inflammation and higher levels of neutrophil infiltration in the ceca of Akt2 KO mice. Flow cytometry analysis further confirmed an increase in the recruitment of Gr-1(+) CD11b(+) neutrophils and F4/80(+) CD11b(+) macrophages in the intestines of infected Akt2 KO mice. Additionally, enhanced levels of annexin V(+) and terminal transferase dUTP nick end labeling-positive (TUNEL(+)) apoptotic cells in the intestines of infected Akt2 KO mice were also observed, indicating that Akt2 plays an essential role in protection against apoptosis. Finally, the differences in bacterial loads and cecal inflammation in WT and Akt2 KO mice infected with WT Salmonella were abolished when these mice were infected with the sopB deletion mutant, indicating that SopB may play a role in protecting the mice from Salmonella infection through the activation of Akt2. These data demonstrate a definitive phenotypic abnormality in the innate response in mice lacking Akt2, underscoring the important protective role of Akt2 in Salmonella infection.